Palliative versus intensive care from the perspective of the medical rescue service - Knor, Jiří; Kabelka, Ladislav; Pekara, Jaroslav; Slabý, Marek; Dušek, Ladislav (Casopis lekaru ceskych, 2024)
According to surveys conducted over the last 10 years, more than 80 % of our population want to live with their loved ones at the end of life. With the ageing of the population and the success of medicine in the early stages of terminal illness, the trajectory and needs at the end of life are gradually changing. The need for health care support is increasing, and for most patients this means the need for 24/7 availability of health care, in this context in the home environment of the terminally ill patient. The question of how palliative care should be organised in an appropriate, meaningful and effective way, the role of specialised health care teams (mobile specialised palliative care), the role of general practitioners, and if, when and how the medical rescue service should/could/should effectively intervene in care, is becoming increasingly urgent. The article combines the experiences and views of an emergency physician and a doctor specialising in geriatrics and palliative medicine.
Keywords: paliativní péče; Terminal Care; Critical Care; Humans; péče o umírající; lidé; péče o pacienty v kritickém stavu; Palliative Care; palliative care, medical rescue service, mobile specialized palliative care, cardiac arrest, cardiopulmonary resuscitation